Analisis Kesesuaian Alih Fungsi Lahan dengan RDTR - Ramadhan, Muhammad Daiyan; Joyodiningrat, Muhammad Henry; Nuryaman, Adi Bima (Universitas Pendidikan Ganesha, 2024)
The ever-increasing population has resulted in the need for land increasing. In response to this, careful anticipation, planning, monitoring and evaluation are needed in setting the Detailed Spatial Planning Plan (RDTR). This research examines land changes that occurred between 2013 and 2023 to see the dynamics of growth that occurred. Apart from that, this research also reviews the suitability of land use with the use of satellite imagery and applicable RDTR maps by providing responses and recommendations for cases that occur. The use of a quantitative approach with descriptive methods and survey methods shows that research results show that there are land changes that have occurred, namely an increase in the area of ​​settlements and a reduction in the area of ​​green open spaces for nature conservation, RTNH, river borders and Sutet borders. The mismatch between land use and land capability class has the potential to degrade land resources and hinder the region's ability to implement its programs, so it is necessary to provide land use regulations in the Coblong District area that are adapted to spatial developments.